Titanium-containing silicon borate catalyst with integral structure as well as preparation method and application of titanium-containing silicon borate catalyst
By preparing a titanium borolate catalyst with an integral structure, the existing mesoporous titanium silicon molecular sieve catalysts have poor stability and low titanium utilization in epoxidation reactions are solved, and higher reaction performance and product selectivity are achieved, which is suitable for epoxidation reactions of macromolecular organic oxidants.
Patent Information
- Application Number
- CN202411622527.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
The existing mesoporous titanium silicon molecular sieve catalysts have poor stability, low titanium utilization rate and insufficient pore size in the epoxidation reaction, which limits its performance in the epoxidation reaction of the propylene.
A titanium borosilicate catalyst adopts an integral structure, and its crystal framework is composed of titanium, silicon, boron and oxygen elements. It is prepared by mechanical twist forming, hydrothermal crystallization and acid treatment steps to form a catalyst with an open pore structure and a high outer specific surface area.
It significantly improves the reaction performance of the catalyst, improves the selectivity and yield of the target product, extends the life of the catalyst, and simplifies the preparation process, which is suitable for continuous fixed bed epoxidation reaction of olefins and organic peroxides.
Smart Images

Figure CN119500256A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic catalysts and their application, in particular to an integral titanium-containing borosilicate catalyst and a preparation method thereof and an application thereof in catalyzing a continuous fixed-bed epoxidation reaction of olefins and organic peroxides. Background Art
[0002] The large-scale industrial production of oxygen-containing chemical products has promoted the rapid development and functional improvement of modern chemical materials. Taking propylene oxide (PO), a representative bulk oxygen-containing chemical, as an example, it plays an extremely important role in the fields of petrochemicals, organic chemicals and polymer materials. PO is a colorless, volatile liquid with an ether-like odor. As an important organic chemical raw material, nearly three-quarters of propylene oxide is used to produce polyether polyols, which are further processed to synthesize polyurethanes, and the rest is used to produce other fine chemicals such as propylene glycol, alcohol ethers, and propylene carbonate. At present, the main methods for industrial production of propylene oxide are: chlorohydrin method, ethylbenzene hydroperoxide method, tert-butyl hydroperoxide method, isopropylbenzene hydroperoxide method (CHPPO) and direct oxidation of hydrogen peroxide. The chlorohydrin method has many problems such as severe equipment corrosion, large consumption of chlorine, and severe environmental pollution; the three co-oxidation methods can effectively solve the above process drawbacks and are green industrial reaction processes (Chin. J. Catal., 2009, 30, 12). Among them, CHPPO technology was first successfully developed by a Czech chemical company and later industrialized by Sumitomo Chemical Company of Japan. In industry, mesoporous titanium silicalite is generally used as a catalyst for the CHPPO process because its larger pores are conducive to the diffusion of macromolecular organic oxidants. However, the amorphous pore wall structure of the mesoporous molecular sieve leads to its poor stability and hydrothermal stability, which seriously affects the life of the catalyst. Mesoporous titanium silicalite usually needs to be silanized to quench the silanol groups on the surface of its pore wall before it can be used, and the coordination state of titanium is poor and the utilization rate is low. Therefore, the development of crystalline large-microporous titanium silicalite catalysts with good stability, low cost and high titanium utilization is a top priority for promoting the propylene epoxidation reaction of macromolecular organic oxidants.
[0003] Crystalline microporous molecular sieves have the characteristics of clear structure and uniform pore distribution. The titanium silicon molecular sieve obtained after the introduction of heteroatom titanium has a stable structure, strong hydrophobicity, and good titanium coordination state. It has been widely used in many oxidation reactions. The first generation of titanium silicon molecular sieve TS-1 with MFI topology has been industrialized in the hydrogen peroxide direct oxidation process (HPPO) process. However, the pore size of the 10-membered ring in TS-1 is relatively narrow, only 0.51-0.56nm, which seriously restricts the diffusion of the substrate, resulting in its poor performance in the epoxidation reaction involving macromolecular organic oxides (Applied Catalysis A: General, 1999, 185, 11). Therefore, designing and synthesizing new titanium silicon molecular sieves with larger pore size is one of the research hotspots. Based on the structural flexibility and modifiability of layered molecular sieve precursors, the controllable modulation of the interlayer connection mode is one of the effective strategies for creating titanium silicon molecular sieve catalysts with excellent diffusion performance and increased pore size. By utilizing the modifiable characteristics of its precursor structure, layer peeling, interlayer pore expansion, etc., a more efficient titanium silicalite catalyst can be constructed, which is expected to achieve the selective oxidation of olefins to prepare epoxides in a catalytic system containing macromolecular organic oxidants.
[0004] The raw powder of synthetic titanium silicon molecular sieve is generally nano-scale or micron-scale powder with small particle size, difficult separation and recovery, and cannot be directly applied to industrial production. In the actual industrial application process, the raw powder of titanium silicon molecular sieve needs to be processed into a shaped catalyst with a certain macroscopic appearance and good mechanical strength to meet the size requirements of different reactors for catalysts. Especially for fixed bed reactors, the catalyst molding step is particularly important. Many factors in the molding process affect the reaction performance of the final shaped catalyst. The introduction of binders usually causes varying degrees of blockage in the pores of the molecular sieve, and also brings some new acid centers, which have negative, competitive or synergistic effects on the reaction performance. Summary of the invention
[0005] The purpose of the present invention is to provide a monolithic titanium borosilicate catalyst and its preparation method and application in view of the shortcomings of the prior art. The monolithic titanium borosilicate catalyst is composed of titanium, silicon, boron and oxygen elements to form a monolithic crystal framework. The main chemical elements of the catalyst are Ti x B y SiO z, x and y range from 0.005 to 0.05 and 0.001 to 0.1, respectively, z = (4×x+3×y+4) / 2. The catalyst is prepared by mechanically twisting and extruding amorphous silicon oxide, titanium oxide and alkali metal oxide, and then mixing with an aqueous solution of a cyclic organic amine and a boron source, followed by hydrothermal crystallization and acid washing. The crystal structure of the catalyst shows a unique X-ray powder diffraction pattern, has an open pore structure and a high external specific surface area, and has high mechanical strength. It is suitable for catalyzing the epoxidation reaction of different olefins with an organic peroxide reagent to prepare the corresponding organic epoxide, showing high selectivity and high product yield. The titanium borosilicate catalyst prepared by the present invention has the technical characteristics of a new type of titanium silicon molecular sieve material that is first formed, then crystallized and treated with acid to form a non-TS-1 crystal structure. At the same time, the fully crystalline integral structure can eliminate the negative effects of amorphous binders on the catalytic center covering and pore blocking, and has many advantages such as simple integration method, short preparation process and high efficiency in the process of catalyzing propylene and organic peroxidation reagents to produce organic epoxides. In the catalytic olefin epoxidation reaction, the reaction performance is significantly improved, with higher target product selectivity and yield, showing good application prospects for olefin liquid phase selective oxidation reactions.
[0006] The object of the present invention is achieved by: a monolithic titanium borosilicate catalyst, characterized in that the crystal skeleton is composed of titanium, silicon, boron and oxygen elements and the morphology is a monolithic titanium borosilicate catalyst in a sheet-like structure, and the atomic composition is expressed in the form of anhydrous oxide as follows: x B y SiO z , x and y range from 0.005 to 0.05 and 0.001 to 0.1, respectively, z = (4 × x + 3 × y + 4) / 2. The characteristic lines of the powder X-ray diffraction spectrum are shown in Table 1, Cu-Kα,
[0007] Table 1: Powder X-ray diffraction data of monolithic titanium-containing borosilicate catalysts
[0008]
[0009]
[0010] In the table: (a) the intensity value of the strongest diffraction peak in the powder X-ray diffraction spectrum is 100, and the relative percentage values of other diffraction peaks to the strongest diffraction peak are defined as their relative intensity levels: W (weak) is ≤20; M (medium) is 20-50; S (strong) is 50-60; VS (very strong) is 60-100.
[0011] A method for preparing a monolithic titanium-containing borosilicate catalyst is characterized in that the preparation method is divided into three steps: twisting and forming, hydrothermal crystallization and acid treatment, as follows:
[0012] Step 1: Mix an inorganic silicon oxide source (calculated as SiO2), a titanium source (calculated as TiO2), an alkali metal source (calculated as Na2O) and water (calculated as H2O) in a molar ratio of 1.0: (0.005-0.05): (0.01-0.1): (1-5), and use a mechanical stirrer to mix and twist for 1-3 hours at room temperature until a uniform wet dough is obtained; then use an extruder to extrude a strip, dry it at 50-100°C for 5-12 hours, and roast it in a muffle furnace at 450-650°C for 4-10 hours. The inorganic silicon oxide source is a mixture of one or more of silica sol, tetraethyl orthosilicate, white carbon black, and fuming silica gel; the titanium source is a mixture of one or more of tetrabutyl titanate, titanium sulfate, titanium nitrate, hexafluorotitanic acid, and ammonium hexafluorotitanate; and the alkali metal source is a mixture of one or more of sodium hydroxide, sodium carbonate, sodium sulfate, and sodium borate.
[0013] Step 2: Add the calcined strips obtained in the first step into a mixture containing a boron source, a cyclic organic amine and water and soak them at room temperature for 1 to 5 hours. The molar ratio of the boron source (calculated as B2O3) to the strips (calculated as SiO2) is 0.05 to 1, the molar ratio of the cyclic organic amine to the strips (calculated as SiO2) is 0.05 to 2, and the mass ratio of water to the strips (calculated as SiO2) is 3 to 10. Then place the above mixture at 150 to 170°C for crystallization for 5 to 10 days. After the crystallization is completed, filter the strips and wash them with deionized water, dry them at 50 to 100°C for 5 to 12 hours, and obtain a strip-shaped monolithic titanium borosilicate catalyst precursor. The boron source is one or a mixture of two or more of sodium borohydride, borax, boric acid, potassium borohydride or sodium borate. The chemical structure of the cyclic organic amine is as follows:
[0014]
[0015] The number of carbon atoms n of the alkyl chain on the cyclic organic amine is 1 to 3, and R is a ring substituent group, including a proton, a methyl group, an ethyl group or a propyl group.
[0016] Step 3: Treat the strip-shaped monolithic titanium borosilicate catalyst precursor obtained in step 2 with an acid solution to wash and extract the sodium oxide therein. The precursor strips and an acid solution with a concentration of 0.2 to 2 mol / L are prepared into a solid-liquid mixture in a mass ratio of 1: (5 to 30), and statically treated at 30 to 80°C for 0.5 to 5 hours. The acid solution is an inorganic acid, including one or a mixture of two or more of hydrochloric acid, nitric acid or sulfuric acid. The strips after acid treatment are filtered and washed with deionized water, dried at 50 to 100°C for 5 to 12 hours, and then calcined in a muffle furnace at 450 to 650°C for 4 to 10 hours to obtain a monolithic titanium borosilicate catalyst.
[0017] An application of a monolithic titanium borosilicate catalyst is characterized in that the catalyst is used for continuous fixed-bed epoxidation of olefins and organic peroxides, and the specific operation is as follows:
[0018] Step 1: The solvent, olefin, and organic peroxide are sequentially passed through a fixed bed reactor filled with a monolithic titanium borosilicate catalyst through a high-pressure plunger pump, and the temperature of the fixed bed reactor is controlled to be 40-100°C, and the pressure of the reaction system is 0.5-4MPa. Among them, the mass ratio of organic peroxide to solvent is 1:1-5; the molar ratio of organic peroxide to olefin is 1:3-15; the feed mass space velocity of organic peroxide is 0.5-5h -1 The solvent may be a protic solvent MOH, wherein M=proton, methyl, ethyl or tert-butyl, or an aprotic solvent such as acetonitrile, decane, benzene, ethylbenzene or isopropylbenzene; the organic peroxide is NOOH, wherein the organic group N=tert-butyl, cyclohexyl, phenethyl or isopropylbenzene; the olefin is a linear or cyclic olefin having a carbon number not greater than 6.
[0019] Step 2: The reaction solution was collected every 2 to 20 hours and analyzed by gas chromatography to obtain the content of the epoxy organic product.
[0020] Compared with the prior art, the present invention has the technical characteristics of forming first and then crystallizing, which can eliminate the negative effects of amorphous binders on factors such as catalytic center coverage and pore blocking, and the integrated method is simple, the preparation process is short and the production efficiency is high. The titanium-containing borosilicate catalyst has a high external specific surface area, which is conducive to the diffusion of macromolecular organic oxides close to the Ti active center, and the reaction performance in the catalytic olefin epoxidation reaction is significantly improved, with higher target product selectivity and yield, showing good application prospects for olefin liquid phase selective oxidation reactions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the X-ray diffraction spectrum of the monolithic titanium-containing borosilicate catalyst prepared in Example 1;
[0022] Figure 2 This is a scanning electron microscope image of the monolithic titanium-containing borosilicate catalyst prepared in Example 1;
[0023] Figure 3 This is the nitrogen adsorption-desorption curve distribution diagram of the monolithic titanium-containing borosilicate catalyst prepared in Example 1. DETAILED DESCRIPTION
[0024] The preparation of the present invention is further described in detail below through specific examples, and only key technical data are listed for each step for simplicity. All embodiments are operated according to the operating steps of the technical scheme. Any simple modification and modification in any form made to the implementation case of the present invention are within the protection scope of the technical scheme of the present invention. Other fine-tuning of any operation and conditions such as the feeding ratio, temperature, and synthesis process of the present invention are considered to infringe the rights and interests of the present invention.
[0025] Example 1
[0026] Step 1: Mix fuming silica gel (calculated as SiO2), tetrabutyl titanate (calculated as TiO2), sodium hydroxide (calculated as Na2O) and water (calculated as H2O) in a molar ratio of 1.0:0.025:0.02:4, and knead them at room temperature using a mechanical stirrer for 2 hours until a uniform wet dough is obtained, and then extrude them into strips using an extruder, dry them at 80°C for 10 hours, and then bake them at 500°C in a muffle furnace for 6 hours.
[0027] Step 2: Add the calcined strips obtained in the first step into a mixture containing boric acid, cyclic organic amine and water and soak at room temperature for 2 hours, the molar ratio of boric acid (calculated as B2O3) to strips (calculated as SiO2) is 0.5, the molar ratio of cyclic organic amine piperidine to strips (calculated as SiO2) is 1.4, and the mass ratio of water to strips (calculated as SiO2) is 7. Then, the above mixture is placed at 165°C for crystallization for 6 days. After the crystallization is completed, the strips are washed with deionized water and dried at 80°C for 8 hours to obtain a strip-shaped monolithic titanium-containing borosilicate catalyst precursor.
[0028] Step 3: The strip-shaped monolithic titanium borosilicate catalyst precursor obtained in step 2 is treated with an acid solution to wash and extract the sodium oxide therein. The precursor strip and a 1.5 mol / L sulfuric acid solution are prepared into a solid-liquid mixture in a mass ratio of 1:10 and statically treated at 50°C for 3 hours. The acid-treated strips are filtered and washed with deionized water, dried at 80°C for 6 hours, and then calcined at 500°C in a muffle furnace for 6 hours to obtain a monolithic titanium borosilicate catalyst, and the mechanical strength is measured to be 50N / cm.
[0029] See also Figure 1The monolithic titanium borosilicate catalyst prepared above has good crystallinity and has the X-ray diffraction structure data shown in Table 1 below, Cu-Kα,
[0030] Table 1: X-ray diffraction structure data of monolithic titanium-containing borosilicate catalyst
[0031]
[0032]
[0033] (a) The intensity value of the strongest diffraction peak in the powder X-ray diffraction spectrum is designated as 100, and the relative percentage values of other diffraction peaks to the strongest diffraction peak are defined as their relative intensity levels: W (weak) is ≤20; M (medium) is 20-50; S (strong) is 50-60; VS (very strong) is 60-100.
[0034] See also Figure 2 The powder sample of the monolithic titanium borosilicate catalyst prepared in Example 1 after crushing showed through scanning electron microscope photographs that it had a plate-like crystal morphology with a length of 50 to 500 μm and a thickness of 50 to 200 nm, and there was no amorphous phase coexisting.
[0035] See also Figure 3 The nitrogen adsorption and desorption characterization of the monolithic titanium-containing borosilicate catalyst prepared in Example 1 showed that its structure had a typical microporous structure, and the rapid increase in adsorption amount in the high specific pressure region of specific pressure > 0.8 indicated that it had a porous characteristic with a high external specific surface area.
[0036] Example 2
[0037] Step 1: Tetraethyl orthosilicate (calculated as SiO2), titanium nitrate (calculated as TiO2), sodium carbonate (calculated as Na2O) and water (calculated as H2O) are mixed in a molar ratio of 1.0:0.033:0.025:3, and kneaded at room temperature for 3 hours using a mechanical stirrer until a uniform wet dough is obtained; then, the dough is extruded and formed using an extruder to produce strips, which are dried at 70°C for 8 hours and calcined in a muffle furnace at 550°C for 6 hours.
[0038] Step 2: Add the calcined strips obtained in the first step into a mixture containing sodium borohydride, cyclic organic amine and water and soak at room temperature for 3 hours, the molar ratio of sodium borohydride (calculated as B2O3) to the strips (calculated as SiO2) is 0.7, the molar ratio of cyclic organic amine hexamethyleneimine to the strips (calculated as SiO2) is 1.0, and the mass ratio of water to the strips (calculated as SiO2) is 8. Then place the above mixture at 155°C for crystallization for 7 days, after the crystallization is completed, wash the strips with deionized water, and dry them at 70°C for 10 hours to obtain a strip-shaped monolithic titanium-containing borosilicate catalyst precursor.
[0039] Step 3: The strip-shaped monolithic titanium borosilicate catalyst precursor obtained in step 2 is treated with an acid solution to wash and extract the sodium oxide therein. The precursor strip and a 1 mol / L nitric acid solution are prepared into a solid-liquid mixture in a mass ratio of 1:8 and statically treated at 60°C for 2 hours. The strips after acid treatment are filtered and washed with deionized water, dried at 70°C for 7 hours, and then calcined at 550°C in a muffle furnace for 4 hours to obtain a monolithic titanium borosilicate catalyst.
[0040] Example 3
[0041] The catalytic performance of the catalyst was evaluated by fixed-bed propylene epoxidation reaction. The reaction was carried out in a sealed high-pressure fixed-bed reactor. The specific operation steps were as follows: the material flowed through a fixed-bed reactor filled with a monolithic titanium borosilicate catalyst (one for propylene delivery and one for ethylbenzene peroxide ethylbenzene solution) by two high-pressure plunger pumps. The fixed-bed reactor was immersed in a constant temperature water bath to control the temperature at 95°C. The mass ratio of the oxide ethylbenzene peroxide to the solvent ethylbenzene was 1:2.5; the molar ratio of the oxide ethylbenzene peroxide to the reaction substrate propylene was 1:4; the feed mass space velocity of the oxide isopropylbenzene peroxide was 1.5h -1 ; The titanium borosilicate catalyst in Example 1 was loaded with a mass of 2.5 g; the reaction system pressure was 3.4 MPa. Every 4 hours, 4 g of the reaction solution was collected, and the content of the epoxy organic product was obtained by gas chromatography analysis. The average yield of propylene oxide within 1600 hours was 93.3%, and the average selectivity of propylene oxide was 99.5%. The catalytic performance comparison of the monolithic titanium borosilicate catalyst and the Ti-HMS mesoporous catalyst is shown in Table 2:
[0042] Table 2: Comparison of catalytic performance of monolithic titanium-containing borosilicate catalyst and Ti-HMS mesoporous catalyst
[0043] Average yield of propylene oxide (%) Average selectivity of propylene oxide (%) Lifespan (h) Example 3 93.3 99.5 1600 Comparative Example 1 86.1 98.1 600
[0044] The Ti-HMS mesoporous molecular sieve catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Polyurethane Industry, 2013, 28, 6), and the reaction conditions were the same as those in Example 3. The gas chromatography data proved that the catalytic performance of the monolithic titanium borosilicate catalyst used in Example 3 in the propylene epoxidation reaction was much higher than that of the Ti-HMS mesoporous molecular sieve catalyst used in the comparative example.
[0045] Example 4
[0046] The catalytic performance of the catalyst was evaluated by fixed-bed propylene epoxidation reaction. The reaction was carried out in a sealed high-pressure fixed-bed reactor. The specific operation steps were: the material was passed through a fixed-bed reactor filled with a monolithic titanium borosilicate catalyst by two high-pressure plunger pumps (one for propylene delivery and one for cumene hydroperoxide cumene solution delivery), and the fixed-bed reactor was immersed in a constant temperature water bath to control the temperature at 90°C. The mass ratio of the oxide cumene hydroperoxide to the solvent cumene was 1:2; the molar ratio of the oxide cumene hydroperoxide to the reaction substrate propylene was 1:5; the feed mass space velocity of the oxide cumene hydroperoxide was 2h -1 ; The loading mass of the titanium borosilicate catalyst in Example 1 was 2 g; the reaction system pressure was 3.2 MPa. 5 g of the reaction solution was collected every 5 hours, and the content of the epoxy organic product was obtained by gas chromatography analysis. The average yield of propylene oxide within 900 hours was 91.4%, and the average selectivity of propylene oxide was 99.7%. The catalytic performance comparison of the monolithic titanium borosilicate catalyst and the Ti-HMS mesoporous catalyst is shown in Table 3:
[0047] Table 3: Comparison of catalytic performance of monolithic titanium-containing borosilicate catalyst and Ti-HMS mesoporous catalyst
[0048] Average yield of propylene oxide (%) Average selectivity of propylene oxide (%) Lifespan (h) Example 4 91.4 99.7 900 Comparative Example 1 85.7 98.3 350
[0049] The Ti-HMS mesoporous molecular sieve catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Polyurethane Industry, 2013, 28, 6), and the reaction conditions were the same as those in Example 4. The gas chromatography data proved that the catalytic performance of the monolithic titanium borosilicate catalyst used in Example 4 in the propylene epoxidation reaction was much higher than that of the Ti-HMS mesoporous molecular sieve catalyst used in the comparative example.
[0050] Example 5
[0051] The catalytic performance of the catalyst was evaluated by the fixed-bed butene epoxidation reaction. The reaction was carried out in a sealed high-pressure fixed-bed reactor. The specific operation steps were as follows: the material was passed through a fixed-bed reactor filled with a monolithic titanium borosilicate catalyst (one for butene delivery and one for tert-butyl hydroperoxide aqueous solution) by two high-pressure plunger pumps. The fixed-bed reactor was immersed in a constant temperature water bath to control the temperature at 70°C. The mass ratio of oxide tert-butyl hydroperoxide to solvent water was 1:3; the molar ratio of oxide tert-butyl hydroperoxide to reaction substrate butene was 1:7; the feed mass space velocity of oxide tert-butyl hydroperoxide was 1.5h -1 ; The loading mass of the titanium borosilicate catalyst in Example 1 was 3 g; the reaction system pressure was 3.6 MPa. Every 10 hours, 6 g of the reaction solution was collected and the content of the epoxy organic product was obtained by gas chromatography. The average yield of butylene oxide within 550 hours was 85.9%, and the average selectivity of butylene oxide was 98.4%. The catalytic performance comparison between the monolithic titanium borosilicate catalyst and the Ti-HMS mesoporous catalyst is shown in Table 4:
[0052] Table 4: Comparison of catalytic performance of monolithic titanium-containing borosilicate catalyst and Ti-HMS mesoporous catalyst
[0053] Average yield of butylene oxide (%) Average selectivity of butylene oxide (%) Lifespan (h) Example 5 85.9 98.4 550 Comparative Example 1 78.2 96.1 140
[0054] The Ti-HMS mesoporous catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Polyurethane Industry, 2013, 28, 6), and the reaction conditions were the same as those in Example 5. The gas chromatography data proved that the catalytic performance of the monolithic titanium borosilicate catalyst used in Example 5 in the propylene epoxidation reaction was much higher than that of the Ti-HMS mesoporous molecular sieve catalyst used in the comparative example.
[0055] Example 6
[0056] The catalytic performance of the catalyst was evaluated by the fixed-bed cyclohexene epoxidation reaction. The reaction was carried out in a sealed high-pressure fixed-bed reactor. The typical operation steps were: the material was passed through a fixed-bed reactor filled with a monolithic titanium borosilicate catalyst by two high-pressure plunger pumps (one for the delivery of cyclohexene and one for the delivery of a mixed solution of cyclohexyl hydroperoxide and acetonitrile). The fixed-bed reactor was immersed in a constant temperature water bath to control the temperature at 60°C. The mass ratio of the oxide cyclohexyl hydroperoxide to the solvent acetonitrile was 1:4; the molar ratio of the oxide cyclohexyl hydroperoxide to the reaction substrate cyclohexene was 1:10; the feed mass space velocity of the oxide cyclohexyl hydroperoxide was 1h -1; The loading mass of the titanium borosilicate catalyst in Example 2 was 4 g; the reaction system pressure was 3.0 MPa. Every 6 hours, 7 g of the reaction solution was collected and the content of the epoxy organic product was obtained by gas chromatography. The average yield of cyclohexene oxide within 320 hours was 78.4%, and the average selectivity of cyclohexene oxide was 82.4%. The catalytic performance comparison of the monolithic titanium borosilicate catalyst and the Ti-HMS mesoporous catalyst is shown in Table 5:
[0057] Table 5: Comparison of catalytic performance of monolithic titanium-containing borosilicate catalyst and Ti-HMS mesoporous catalyst
[0058] Average yield of cyclohexene oxide (%) Average selectivity of cyclohexene oxide (%) Lifespan (h) Example 6 78.4 82.4 320 Comparative Example 1 55.1 78.9 90
[0059] The Ti-HMS mesoporous catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Polyurethane Industry, 2013, 28, 6), and the reaction conditions were the same as those in Example 6. The gas chromatography data proved that the catalytic performance of the monolithic titanium borosilicate catalyst used in Example 6 in the propylene epoxidation reaction was much higher than that of the Ti-HMS mesoporous molecular sieve catalyst used in the comparative example.
[0060] Example 7
[0061] The catalytic performance of the catalyst was evaluated by the fixed-bed cyclohexene epoxidation reaction. The reaction was carried out in a sealed high-pressure fixed-bed reactor. The typical operation steps were: the material was passed through a fixed-bed reactor filled with a monolithic titanium borosilicate catalyst by two high-pressure plunger pumps (one for the delivery of cyclohexene and one for the delivery of ethylbenzene hydroperoxide ethylbenzene solution), and the fixed-bed reactor was immersed in a constant temperature water bath to control the temperature at 75°C. The mass ratio of the oxide ethylbenzene hydroperoxide to the solvent ethylbenzene was 1:3.5; the molar ratio of the oxide ethylbenzene hydroperoxide to the reaction substrate cyclohexene was 1:12; the feed mass space velocity of the oxide ethylbenzene hydroperoxide was 2.4h -1 ; The loading mass of the titanium borosilicate catalyst in Example 2 was 4.5 g; the pressure of the reaction system was 3.6 MPa. 3 g of the reaction solution was collected every 8 hours, and the content of the epoxy organic product was obtained by gas chromatography analysis. The average yield of cyclohexene oxide within 720 hours was 81.4%, and the average selectivity of cyclohexene oxide was 85.7%. The catalytic performance comparison of the monolithic titanium borosilicate catalyst and the Ti-HMS mesoporous catalyst is shown in Table 6:
[0062] Table 6: Comparison of catalytic performance of monolithic titanium-containing borosilicate catalyst and Ti-HMS mesoporous catalyst
[0063] Average yield of cyclohexene oxide (%) Average selectivity of cyclohexene oxide (%) Lifespan (h) Example 7 81.4 85.7 720 Comparative Example 1 62.4 77.2 180
[0064] The Ti-HMS mesoporous catalyst used in Comparative Example 1 was synthesized according to the method in the literature (Polyurethane Industry, 2013, 28, 6), and the reaction conditions were the same as those in Example 7. The gas chromatography data proved that the catalytic performance of the monolithic titanium borosilicate catalyst used in Example 7 in the propylene epoxidation reaction was much higher than that of the Ti-HMS mesoporous molecular sieve catalyst used in the comparative example.
[0065] The protection content of the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the inventive concept, changes and advantages that can be thought of by those skilled in the art are included in the present invention and are protected by the attached claims.
Claims
1. A monolithic titanoborosilicate catalyst, characterized in that: Titanium borosilicate catalysts are composed of titanium, silicon, boron and oxygen elements, which have a flaky monolithic crystal framework. The chemical formula is: Ti x B y SiO z , wherein the value ranges of x and y are 0.005 to 0.05 and 0.001 to 0.1, respectively, and z = (4×x+3×y+4) / 2; the titanoborosilicate catalyst has X-ray diffraction data of the diffraction peaks shown in Table 1 below, Cu-Kα, Table 1: Powder X-ray diffraction data of monolithic titanium-containing borosilicate catalysts In the table: (a) is the relative intensity level of the diffraction peak in the powder X-ray diffraction spectrum; W is the weak diffraction peak; M is the medium diffraction peak; S is the strong diffraction peak; VS is the strongest diffraction peak.
2. A method for preparing the monolithic titanium-containing borosilicate catalyst according to claim 1, characterized in that: The preparation of the monolithic titanium-containing borosilicate catalyst specifically comprises the following steps: Step 1: Mix an inorganic silicon oxide source calculated as SiO2, a titanium source calculated as TiO2, an alkali metal source calculated as Na2O and deionized water in a molar ratio of 1.0: 0.005-0.05: 0.01-0.1: 1-5, stir at room temperature for 1-3 hours, extrude the uniformly mixed wet dough into strips, dry at 50-100°C for 5-12 hours, and roast the dried strips at 450-650°C for 4-10 hours. The inorganic silicon oxide source is one or a mixture of two or more selected from silica sol, tetraethyl orthosilicate, white carbon black and fuming silica gel; the titanium source is one or a mixture of two or more selected from tetrabutyl titanate, titanium sulfate, titanium nitrate, hexafluorotitanic acid and ammonium hexafluorotitanate; and the alkali metal source is one or a mixture of two or more selected from sodium hydroxide, sodium carbonate, sodium sulfate and sodium boride. Step 2: Place the calcined strips into a solution of a boron source, a cyclic organic amine and deionized water, soak at room temperature for 1 to 5 hours, crystallize the soaked strips at 150 to 170°C for 5 to 10 days, filter out the strips and wash them with deionized water, and dry them at 50 to 100°C for 5 to 12 hours to obtain a precursor strip. The molar ratio of the boron source in terms of B2O3 to the strips in terms of SiO2 is 0.05 to 1; the molar ratio of the cyclic organic amine to the strips in terms of SiO2 is 0.05 to 2; the mass ratio of the deionized water to the strips in terms of SiO2 is 3 to 10; the boron source is one or a mixture of two or more of sodium borohydride, borax, boric acid, potassium borohydride and sodium borate; the cyclic organic amine is an organic compound of the following structural formula: Wherein, n is a carbon atom on the alkyl chain, n=1 to 3; R is a ring substituent including a proton, a methyl group, an ethyl group or a propyl group; Step 3: Prepare a solid-liquid mixture of the precursor strips and an acid solution with a concentration of 0.2 to 2 mol / L in a mass ratio of 1:5 to 30, and let it stand at a temperature of 30 to 80°C for 0.5 to 5 hours. The strips after acid treatment are filtered and washed with deionized water, and dried at a temperature of 50 to 100°C for 5 to 12 hours. The dried strips are calcined at a temperature of 450 to 650°C for 4 to 10 hours to obtain a flaky columnar product as an integral titanium borosilicate catalyst, and the acid solution is one or a mixture of two or more of hydrochloric acid, nitric acid and sulfuric acid.
3. An application of the monolithic titanium-containing borosilicate catalyst according to claim 1, characterized in that: The monolithic titanium borosilicate catalyst is used to catalyze the epoxidation reaction of different olefins with an organic peroxidation agent to prepare the corresponding organic epoxides, and simultaneously achieve the natural separation of the reaction product and the catalyst. The specific operation is as follows: The solvent, olefin and organic peroxide are sequentially passed through a fixed bed reactor filled with a monolithic titanium borosilicate catalyst for selective oxidation reaction to prepare the corresponding organic epoxide. The temperature of the olefin oxidation reaction is 40-100°C, the reaction pressure is 0.5-4MPa; the mass ratio of the organic peroxide to the solvent is 1:1-5; the molar ratio of the organic peroxide to the olefin is 1:3-15; the feed mass space velocity of the organic peroxide is 0.5-5h -1 ; The solvent is a protic solvent MOH or a non-protonic solvent, and M in the protic solvent MOH is a proton, methyl, ethyl or tert-butyl; the non-protonic solvent is acetonitrile, decane, benzene, ethylbenzene or isopropylbenzene; the organic peroxide is NOOH, in which the organic group N is tert-butyl, cyclohexyl, phenethyl or isopropylbenzene; the olefin is a straight chain or cyclic olefin with a carbon number not greater than 6.